(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: Understanding the characteristics of pediatric patients who died in the Pediatric Intensive Care Unit (PICU) is essential for developing interventions to reduce mortality risk. Methods: A prospective descriptive study was conducted on children aged 1 month to 16 years who died in the PICU. Collected variables included age, gender, source of admission, clinical and laboratory findings, therapeutic interventions before and during PICU stay, and the number of deaths. Data were analyzed according to the study objectives. Categorical variables were expressed as percentages, while continuous variables were expressed as means and standard deviations. Categorical variables were analyzed using the Chi-square (χ²) test or Fisher’s exact test as appropriate. Univariate and multivariate logistic regression analyses were performed to determine the odds ratios (ORs) with 95% confidence intervals (CIs). A two-tailed test was applied, and a p-value of <0.05 was considered statistically significant. Results: From January 2019 to December 2019, there were 306 deaths in the PICU, including 52 deaths within the first 24 hours, corresponding to a mortality rate of 23.9%. Children under 1 year of age accounted for 58.2% of deaths, and 74.6% of fatal cases were transferred from the Emergency and Toxicology Department. The leading causes of death were multiple organ failure (75%), circulatory failure (12.1%), and respiratory failure (8.2%). Multivariate analysis identified independent risk factors for mortality, including age under 1 year, underlying disease, fluid resuscitation prior to PICU admission, mechanical ventilation, use of vasoactive agents during treatment, renal replacement therapy, and multiple organ failure (p < 0.005). Conclusion: Mortality in the PICU remains high, particularly among infants. Most fatal cases were transferred from the Emergency and Toxicology Department, with multiple organ failure being the leading cause of death. Factors such as age under 1 year, underlying disease, pre-admission fluid resuscitation, mechanical ventilation, use of vasoactive drugs, renal replacement therapy, and multiple organ failure were associated with an increased risk of death.